NGARUH FITUR DAN PRESTISE MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK OPPO DI KOTA TERNATE - Ibnu Sina Hi Yusuf (Jurnal Manajemen Sinergi, 2016)
The purpose of this study is to determine the effect of features and prestige Brand OPPO brand smartphone purchase decisions in Ternate City. Quantitative research type. Population in this study of Ternate people’s, smartphone users brand OPPO,Techniques Sampling using purposive sampling method, because using characteristics and criteria. Characteristics and criteria In question is the longest purchase of brand smartphones, OPPO on 3 months ago and mobile phone price   Rp.3.000.000. Number of samples As many as 62 respondents. Analytical techniques used in the study.This is a multiple linear regression analysis operated through SPSS program. The results of this study indicate that feature variables Have a positive and significant effect on purchasing decision Smartphone brand OPPO, brand prestige has a significant and positive influence To the OPPO brand smartphone purchase decision, an influential feature Positive and significant to the brand prestige. This is shown With R square value of 48.5% while the rest 51.7% influenced by Other variables not examined in this study.